The Theory of Interhybridity: Socio-political Dimensions and Migration - Armando Aliu (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
The Western Balkans integration within the EU has started a legal process which is the rejection of former communist legal/political approaches and the transformation of former communist institutions. Indeed, the EU agenda has brought vertical/horizontal integration and Europeanization of national institutions (i.e. shifting power to the EU institutions and international authorities). At this point, it is very crucial to emphasize the fact that the Western Balkans as a whole region has currently an image that includes characteristics of both the Soviet socialism and the European democracy. The EU foreign policies and enlargement strategy for Western Balkans have significant effects on four core factors (i.e. Schengen visa regulations, remittances, asylum and migration as an aggregate process). The convergence/divergence of EU member states' priorities for migration policies regulate and even shape directly the migration dynamics in migrant sender countries. From this standpoint, the research explores how main migration factors are influenced by political and judicial factors such as; rule of law and democracy score, the economic liberation score, political and human rights, civil society score and citizenship rights in Western Balkan countries. The proposal of interhybridity explores how the hybridization of state and non-state actors within home and host countries can solve labor migration-related problems. The economical and sociopolitical labor-migration model of Basu (2009) is overlapping with the multidimensional empirical framework of interhybridity. Indisputably, hybrid model (i.e. collaboration state and non-state actors) has a catalyst role in terms of balancing social problems and civil society needs. Paradigmatically, it is better to perceive the hybrid model as a combination of communicative and strategic action that means the reciprocal recognition within the model is precondition for significant functionality. This will shape social and industrial relations with moral meanings of communication.
Additional information: Munich Personal RePEc Archive Paper No. 44056
Keywords: F22; C1; J61; A1; P48; P4; F5; J6; P3; C8; J5; J53; 300; Interhybridity; Migration; Politics; Western Balkans